The Role Of "Make in India" In Enhancing the Performance and Associated Challenges for Micro, Small and Medium Enterprises In NCR - Sharma, Bhawana; Pandey, Anupama (Journal of Neonatal Surgery, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the foundation of the Indian economy, making substantial contributions to employment, industrial production, and exports. The GOI's "Make in India" project, initiated in 2014, seeks to convert the nation into a worldwide manufacturing center by promoting local output, enticing international investment, and enhancing the business environment. This research evaluates the performance and obstacles encountered with MSMEs within the NCR throughout the context of this project. A mixed-method approach was used to gather primary data from 300 MSME respondents using structured questionnaires, whereas secondary data was sourced from government sources and academic research. The research utilizes statistical methods like correlation, regression, & descriptive statistics to assess critical variables such as production output, employment creation, and international trade. Research demonstrates that the "Make in India" campaign has substantially influenced MSME development, accounting for 80.5% of the variation in manufacturing output. Nonetheless, its impact on job creation and skill enhancement is limited. Moreover, MSMEs have obstacles like financial restrictions, legal hurdles, and technology deficiencies, which impede their complete alignment with the initiative's goals. The research emphasizes the need for specific governmental measures, increased financial accessibility, and upgraded infrastructure to strengthen MSME competitiveness. Confronting these issues is essential for optimizing the advantages of "Make in India" and guaranteeing the sustained advancement of MSMEs as pivotal contributors to India's industrial & economic progress